Modern Full-Stack Development : Using TypeScript, React, Node. js, Webpack, Python, Django, and Docker - Zammetti, Frank W. (Apress L. P., 2022)
Explore what React, Node, Python, Django, TypeScript, Webpack, and Docker have to offer individually, and how they all fit together in modern app development. This updated version will show you how to build apps with React, Node.js or Django, and TypeScript, and how Webpack can be used to optimize and organize your code for deployment. You'll begin by building a solid foundation of knowledge and quickly expand it by constructing three different real-world apps. These aren't just simple, contrived examples but real apps that you can choose to install on your servers and use for real. You'll also understand how Docker can be used to run the apps you build in a clear and well-defined way, all of which will be able to springboard you into creating more advanced apps on your own. You'll see why React is one of the most popular web development tools available today, and why Node.js is also frequently used for server-side development. The fact that both utilize JavaScript is a big selling point, but there are shortcomings. Modern Full-Stack Development highlights how adding Django, Webpack, and Docker to the mix resolves any issues by creating a potent full development stack on which to build applications - two possible stacks, really!! What You'll Learn: Review the basics of TypeScript and writing both React and Node apps with it Construct a project with NPM and Webpack, configuration and usage Utilize client-side and server-side development Employ REST APIs and database usage across two tech stacks, Node and Python/Django Deploy apps using Docker Who This Book Is For: Web developers and software architects.